Flexible nano-liposomes-based transdermal hydrogel for targeted delivery of dexamethasone for rheumatoid arthritis therapy. (31st December 2022) - Zhao, Yi-Pu; Han, Jiang-Fan; Zhang, Fei-Yue; Liao, Tian-Tian; Na, Ren; Yuan, Xiao-Feng; He, Guang-bin; Ye, Weiliang
Abstract: Rheumatoid arthritis (RA) is an inflammatory immune-mediated disease that can lead to synovitis, cartilage destruction, and even joint damage. Dexamethasone (DEX) is a commonly used agent for RA therapy on inflammation manage. However, the traditional administering DEX is hampered by low efficiency and obvious adverse effects. Therefore, in order to efficiently deliver DEX to RA inflamed joints and overcome existing deficiencies, we developed transdermal formation dextran sulfate (DS) modified DEX-loaded flexible liposome hydrogel (DS-FLs/DEX hydrogel), validated their transdermal efficiency, evaluated its ability to target activated macrophages, and its anti-inflammatory effect. The DS-FLs/DEX exhibited excellent biocompatibility, sustainable drug release, and high uptake by lipopolysaccharide (LPS)-activated macrophages. Furthermore, the DS-FLs/DEX hydrogel showed desired skin permeation as compared with regular liposome hydrogel (DS-RLs/DEX hydrogel) due to its good deformability. In vivo, when used the AIA rats as RA model, the DS-FLs/DEX hydrogel can effectively penetrate and accumulate in inflamed joints, significantly improve joint swelling in RA rats, and reduce the destructive effect of RA on bone. Importantly, the expression of inflammatory cytokines in joints was inhibited and the system toxicity did not activate under DS-FLs/DEX hydrogel treatment. Overall, these data revealed that the dextran sulfate (DS) modified DEX-loaded flexible liposome hydrogel (DS-FLs/DEX hydrogel) can prove to be an excellent drug delivery vehicle against RA.